Relationship between soil water content and crop yield under sahelian climate conditions: case study of Tougou experimental site in Burkina Faso - Zoure, Cheick Oumar; KOITA, Mahamadou; Niang, Dial; Baba, Izza Issa; Yonaba, Ousmane Roland; Dara, Amagana Emmanuel; Fow, Tazen; Queloz, Pierre; Karambiri, Harouna (JOURNAL OF ADVANCES IN PHYSICS, 2017)
This study aims at assessing the relationship between soil water stock and the yield of agricultural practices in Tougou catchment located in northern Burkina Faso. It is a region that has experienced a significant and continuous degradation of its natural resources, especially soils, due to the climate variability and the rapid increase of the population. Areas allocated to subsistence agriculture are increasing at the expense of pastoral land. This degradation causes a change in processes and mechanisms that control ecological systems. In order to provide solutions to this issue, some agricultural practices have been implemented to improve crop yield. This is particularly the case of traditional techniques:za, stony line and half-moon, which can significantly improve the soil infiltration capacity and yield. Daily monitoring of soil moisture and pressure in experimental plots based on these agricultural practices show that half-moon and Za¯ provided good yield with 2180kg / ha and 1070 kg / ha respectively compared to that of the control plot with about 480 kg/ha. These important yields are due in large part to the improvement of the retention capacity of these soils, thus giving to crops the necessary water need for their development even in drought periods